Comparative characteristics of the regeneration of the femur bone of rats at intramedullary osteosynthesis using medical steel and carbon-carbon composite material - V. V. Chornyi; P. V. Bohdanov (Zaporozhye State Medical University, 2023)
The aim of this study was to compare the morphological features of rat femoral bone regeneration during intramedullary osteosynthesis using medical steel and carbon-carbon composite material. Materials and methods. All animals were divided into two groups. A fracture of the thighbone was simulated by surgical intervention. In the first group, medical steel was used for intramedullary fixation of fragments; in the second group, fragments were fixed using a carbon-carbon composite material. The morphological, morphometric, histological, histochemical, immunohistochemical and X-ray methods was used, the bone regenerate was studied on the 30th day, 6 and 12 months after the surgical intervention. There were established expression of immunohistochemical markers CD-34 and Ki-67 using the ImageJ program. The statistical analysis of the obtained results was performed by the methods of variational statistics using the program Statistica 13.0. Results. In the group of animals where composite material was used, on the 30th day after surgery, a statistically significant increase in the expression of the relative area occupied by CD-34+ structures compared to the second group of animals was established (4.80 ± 0.40 in the group in which the composite material was used and 2.80 ± 0.30 in group in which the medical steel was used). Also a statistically significant increase in the expression of the Ki-67+ marker was established (5.20 ± 0.36 in the group in which the composite material was used and 2.48 ± 0.32 in group in which the medical steel was used). With inspection microscopy, faster rates of osseointegration and regeneration of the fracture site were observed in the group of animals in which the composite material had been used compared to the other group of animals due to the stimulation of vascular endothelium growth. The data of the histological examination coincide with the data of the X-ray examination at all the periods of observation. Conclusions. The use of carbon-carbon composite material during intramedullary osteosynthesis accelerates bone regeneration pace due to the angiogenic effect, which is confirmed by increase in the expression of markers of proliferative activity Ki-67+ and the marker of vascular endothelium CD-34+ in the group of experimental animals in 30 days.